2013
DOI: 10.1364/oe.21.027759
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon excited fluorescence from a pseudoisocyanine-attached gold-coated tip via a thin tapered fiber under a weak continuous wave excitation

Abstract: A simple tapered fiber based photonic-plasmonic hybrid nanostructure composed of a thin tapered fiber and a pseudoisocyanine (PIC)-attached Au-coated tip was demonstrated. Using this simple hybrid nanostructure, we succeeded in observing two-photon excited fluorescence from the PIC dye molecules under a weak continuous wave excitation condition. From the results of the tip-fiber distance dependence and excitation polarization dependence, we found that using a thin tapered fiber and an Au-coated tip realized ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The AgTip was prepared by sputtering Ag onto a silicon AFM cantilever with a 7 nm tip radius (Olympus, OMCL-AC160TS-R3). The scattering spectrum of the AgTip was measured by contacting the AgTip with a taper fiber coupled with a white light source, 48 and numerical simulations of the AgTip were conducted using finite element analysis. Details are provided in the SI.…”
Section: Nano Lettersmentioning
confidence: 99%
“…The AgTip was prepared by sputtering Ag onto a silicon AFM cantilever with a 7 nm tip radius (Olympus, OMCL-AC160TS-R3). The scattering spectrum of the AgTip was measured by contacting the AgTip with a taper fiber coupled with a white light source, 48 and numerical simulations of the AgTip were conducted using finite element analysis. Details are provided in the SI.…”
Section: Nano Lettersmentioning
confidence: 99%
“…In 2016, Ren et al studied a plasmonic hybrid nanostructure composed of a gold-film coating tipped with a tapered fiber and the pseudoisocyanine (PIC) dye, and 2PE from the PIC dye was detected under a continuous wave (CW) laser at a low irradiation intensity (several tens of kW/cm 2 ). 9 Furthermore, in 2016, Jensen et al fabricated a bowtie aperture substrate coated with a thin silver film, and the optical trapping of QDs and 2PE was detected using a CW laser (1.56 MW/cm 2 ). 10 In 2019, Rabor et al reported the detection of 2PE induced by a picosecond-pulse laser from fluorescence molecules, including rhodamine 6G, fixed to a glass slide modified with a triangular silver nanoprism.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They have also been employed to efficiently couple fluorescence from single-light emitters to single-mode fibers [9][10][11][12][13][14][15][16]. In addition, nanofibers have been used in the generation of supercontinuum [17], two-photon excited fluorescence [18], and more recently in optical tweezers [19].…”
Section: Introductionmentioning
confidence: 99%
“…We consider that the high sensitivity of the transmission degradation of the nanofiber is useful for detecting material differences and nano-structures on the surface of an object. For example, when a nanofiber is vertically moved towards a point on an object, the change in the transmission depends on the material and the structure at that point [18]. Also, when a nanofiber is horizontally scanned over the surface of an object, the distribution of the material and nano-structure on the object can be detected from the transmission change.…”
Section: Introductionmentioning
confidence: 99%